Answers

  • Brainly User
2016-03-07T00:23:10+08:00
Equation 1:  2x + 5y = 9
Equation 2:  -x + y = 2
                           y = x + 2

Solve the system by substitution:

Step 1:  Substitute x + 2 for y in Equation 1:
              2x + 5y = 9
              2x + 5(x+2) = 9
              2x + 5x + 10 = 9
              7x = 9 - 10
              7x/7 = -1/7
              x = -1/7

Step 2:  Substitue -1/7 for x in y = x + 2:
              y = -1/7 + 2
              y = -1/7 + 14/7
              y =   13/7

Check:
2x + 5y = 9
2(-1/7) + 5(13/7) = 9
-2/7 + 65/7 = 9
63/7 = 9
 9 = 9  (true)  
--------------

-x + y = 2
-(-1/7) + 13/7) = 2
1/7 + 13/7 = 2
14/7 = 2
2 = 2   (true)

0